Determining the Origin of Inner Planetary System Debris Orbiting the Dustiest Main Sequence Stars. Issue Volume 8:Issue S293(2012) (29th April 2014) - Melis, Carl; Zuckerman, B.; Rhee, Joseph H.; Song, Inseok; Murphy, S. J.; Bessell, M. S.
Abstract: We develop a means to distinguish between warm dusty circumstellar debris disks produced by steady state collisional evolution of a planetesimal belt or through transient events.